Characterization of groundwater quality in the coastal aquifer of Terengganu, Malaysia - Hamzah, Zahidi (2017)
Rapid developments in agricultural, residential and industrial activities have increased pressure for the public water supply in Terengganu. Groundwater was touted to fulfil the demand thus commanded research on its quality through characterization study. The integration of geochemical methods such as multiple ion ratios and multivariate statistical analysis methods such as FA/PCA were carried out on 169 samples from 29 monitoring wells to characterize and to elucidate the factors and processes that influencing the geochemical composition of groundwater in coastal shallow aquifer of Terengganu. Spatial distribution maps of factors were obtained using geostatistical methods such as Ordinary Kriging. The samplings were carried out twice annually during the wetter Northeast Monsoon and drier Southwest Monsoon, respectively from 2006-2014. Generally, the groundwater is mildly acidic to alkaline in nature. Ca2+, Na" and K+ ions were the dominant cations while HC03- and cr were the leading anions. The abundance of ea2+ were contributed by carbonate and silicate weathering processes while HC03- and cr were resulted from reverse ion exchange reaction as revealed by geochemical modelling using multiple ionic ratios. Saline intrusion probably cause the hydrogeochemical facies dominated by Ca-Mg-HCOrCI type based on Piper diagram plot. CI-;HC03- ratio further reinforced the influence of salinization was caused by seawater intrusion to the aquifer which slighty or moderately affected half (50.9%) of the groundwater samples. Therefore, groundwater in the study area constantly under threat of salinization mostly by seawater intrusion prominently in the major river confluences. Mapping of salinization affected area utilizing geostatistical analyses especially around the wells of Terengganu and Marang River Basin in the northeast, Dungun and Kemaman River confluence in southeast of study area were reliable with acceptable accuracy based on limited and sparsely located monitoring wells. Salinization, anthropogenic activities, reverse ion exchange, weathering processes, agricultural impact and seasonal were the regulating factors that influencing 63% of the major ion chemistry in study area as determined by factor analysis. Conclusively, the finding showed that for effective utilization, aquifer protection and prediction of changes, understanding the groundwater hydrogeochemical characteristics is crucial in order to minimize the effects of salinization and natural weathering processes. Reducing the anthropogenic pollution such as agriculture and urbanization impact also help to preserve and maintain groundwater resources for future usage.